Experimental Research on the Heat Preservation Effect of Water-retaining Roof Bricks in Winter. (2015) - Han, Rubing; Xu, Zhimao; Qing, Yutao; Long, Enshen
Abstract: Roof insulation in winter has an influence on the indoor heat load and causes an increase in the heat on the top room. This paper selects three conditions for testing: (1) comparing a water-retaining roof using bricks with water, a roof with empty bricks and an ordinary roof, (2) comparing different depths of water-retaining roof (from water level h=0 cm to h=12 cm), and (3) comparing ventilated and non-ventilated water-retaining roofs. In analyzing the effect of water-retaining insulation the results show that: the water-retaining roof is more insulated than the non-water-retaining roof; when the water depth is 8 cm there is no relative need to increase the depth of water to increase its insulation effect; and, air layers play an important role in roof insulation. For energy saving in existing buildings using a water-retaining roof will improve the performance of the roof insulation.